Genetic and epigenetic factors: Role in male infertility - M B Shamsi; K Kumar; R Dada (Indian Journal of Urology, 2011)
Genetic factors contribute upto 15%-30% cases of male infertility. Formation of spermatozoa occurs in a sequential manner with mitotic, meiotic, and postmeiotic differentiation phases each of which is controlled by an intricate genetic program. Genes control a variety of physiologic processes, such as hypothalamus-pituitary-gonadal axis, germ cell development, and differentiation. In the era of assisted reproduction technology, it is important to understand the genetic basis of infertility to provide maximum adapted therapeutics and counseling to the couple.